Freelance Market Development Factors - D. Zh. Abdreissova; D. T. Baitenizov; T. A. Azatbek; S. N. Valieva (Экономика: стратегия и практика)
The rapid development of Internet marketing has led to the fact that the active population has become independent of a permanent place of work. Flexible forms of employment have become more popular now, as they allowed the employees to work efficiently, realize their labor potential. The current constraints associated with the pandemic have further increased the relevance of telecommuting. The purpose of the article is to identify and classify the main factors contributing to the growth of the freelance market. To achieve the goal, the methods of analysis and synthesis were used in the framework of the structural-functional approach. The paper reflects the prerequisites and reasons for the emergence of freelancing, and outlines the socio-economic role of freelancing in solving modern problems of employment. The conditions favorable for the active development of the freelance services market are considered, which were classified into price and non-price conditions. Particular attention is paid to the impact of the Internet on the development of freelance services. The authors proposed factors in the freelance market, represented by primary factors, demand factors, supply factors and factors of an individual nature. Within each group they are investigated and substantiated. These factors allowed the authors to form and identify measures aimed at stimulating the development of the freelance market in Kazakhstan. They also proposed to create a multifunctional Internet exchange and gave recommendations to determine its functionality and main characteristics. The implementation of them will provide the freelance market with the necessary digital platform.